Multi-level scenarios for exploring alternative futures for upper tributary watersheds in mainland Southeast Asia - Lebel L. (2014)
Nested scenarios at 2 spatial levels were constructed to explore key uncertainties about how livelihoods and landscapes in upper tributary watersheds of montane mainland Southeast Asia might unfold in the coming decades. At the regional level the scenarios highlight the implications of different forms of market and political integration. At the upper tributary level the scenarios highlight changing dependencies on local natural resources and the extent of empowerment of local stakeholders in their management. The scenarios are intended as a starting point for discussions among stakeholders, as a framework for designing and interpreting land use and land cover change simulation studies, and as a tool to help identify resilient livelihood and regional development strategies. The multi-level approach to scenario building introduced here shows considerable promise for mountain regions, as it encourages analyses to be cognizant of broader-scale economic and social changes as well as the uncertainties specific to these upland environments.